Observation of e(+) e(-) -> eta Y(2175) at center-of-mass energies above 3.7 GeV - Çetin, Serkant Ali (AMER PHYSICAL SOC, 2019)
The state Y(2175) is observed in the process e(+)e(-) -> eta Y(2175) with a statistical significance larger than 10 standard deviations using the data collected with the BESIII detector operating at the BEPCII storage ring at center-of-mass energies between 3.7 and 4.6 GeV. This is the first observation of the Y(2175) in this process. The mass and width of the Y(2175) are determined to be (2135 +/- 8 +/- 9) MeV/e(2) and (104 +/- 24 +/- 12) MeV, respectively, and the production cross section (sigma) of e(+)e(-) -> eta Y(2175) -> eta phi f(0)(980) -> eta phi pi(+)pi(-) is at the several hundred femtobarn level. No significant signal for the process e(+)e(-) -> eta'Y(2175) is observed and the upper limit on sigma(e(+)e(-) -> eta'Y(2175))/sigma(e(+)e(-) -> eta Y(2175)) is estimated to be 0.43 at the 90% confidence level. We also search for psi(3686) -> eta Y(2175). No significant signal is observed, indicating a strong suppression relative to the corresponding J/psi decay, in violation of the "129% rule".
Keywords: Y(2175); STATE